STUDENTS’ PERCEPTION OF USING SOCIAL MEDIA IN WRITING ENGLISH AS A FOREIGN LANGUAGE - Rahmawati, Irma; Susilawati, Endang; Rezeki, Yanti Sri (Indonesian Journal of Educational Development (IJED), 2024)
This study aimed to find out the perception of semester VIII students of the English Language Education Study Program at Universitas Tanjungpura about the most used social media for writing English as a Foreign Language. This study used a descriptive design and a quantitative method. To collect the data, the researcher used a survey through a questionnaire and interview. The population in this study was 81 students, while the sample was 39 students from classes A1, A2, A3, B1, and B2. The instrument for collecting the data was 28-item questionnaires and 4 main questions interviews. The result of this study was that students have positive perceptions with a total of 79%. Furthermore, from the data, it was found that the most used social media for English writing practice was Instagram with a total of 73%. Moreover, the reason students use Instagram to write English is caused by external factors and internal factors. Therefore, students perceive that Instagram is the most appropriate social media to practice English writing skills.